Prevalence of sub-clinical mastitis and its association with milking practices in an intensive dairy production region of Uganda - MIYAMA, Takeshi; BYARUHANGA, Joseph; OKAMURA, Ikuo; NAGAHATA, Hajime; MURATA, Ryo; MWEBEMBEZI, William; MURAMATSU, Yasukazu; MAKITA, Kohei (Journal of Veterinary Medical Science, 2020)
A cross-sectional study was conducted to investigate the risk factors for sub-clinical mastitis (SCM) in Mbarara District, an intensive dairy production region of Uganda where hand-milking is dominant. In 30 farms, herd-level milking practices and SCM prevalence were studied. The SCM prevalences were 68.6% (417/608, 95% confidence interval (CI): 64.9–72.2%) and 39.2% (946/2,411, 37.3–41.2%) at the cow- and quarter-levels, respectively. A preventive factor for SCM was cow calmness at the end of milking (OR: 0.20, 95%CI: 0.05–0.79, P=0.021); a risk factor was rough teat-end (OR: 1.75, 95%CI: 1.14–2.68, P=0.011). Good cow hygiene was negatively associated with environmental mastitis (P=0.002). Appropriate hand-milking practices that avoid teat damage are expected to reduce SCM in Uganda.